Rancang Bangun dan Pengujian Penetrometer Digital dengan Perekam Data Berbasis Android - Budi Priyonggo; I Dewa Made Subrata; Radite Praeko Agus Setiawan (Jurnal Keteknikan Pertanian, 2019)
Abstract Static penetrometer is designed to measure the force that required to push a conical probe of the soil deepness through a constant velocity. The output data are force per unit area without soil factor influenced, i.e. soil moisture content. Soil moisture content is an important factor that affects soil penetration resistance. The soil moisture content method that commonly uses a gravimetric method can takes a long time to obtain data of soil moisture conten. Therefore a penetrometer is needed which can measure the soil moisture content at once. The objective of study is to design and develop static penetrometer equipped with soil moisture sensor and android based data record system. Loadcell and HX711 used as force sensor, HC-SR04 and DHT11 used as depth sensor and a kit soil moisture module has been modified as soil moisture sensor. Calibration and validation result of the sensor shown that the correlation value of R2=0.9994 and R2=0.9995 (force sensor), R2=0.9999 and R2=0.9999 (depth sensor) and R2= 0.9098 and R2=0.9255 (soil moisture sensor). Penetrometer performance test in land result obtained the value of R2=0.9583 for cone index, R2=0.9994 for depth sensor dan R2=0.6673 moisture content sensor. Penetrometer pervormance test in rice field result obtained the value of R2=0.9583 for cone index, R2=0.9941 for depth sensor and R2=0.7201 moisture content sensor. The result of regression anlaysis for moisture content equation obtained value R2=0.7201 for testing on dry land and R2=0.9058 for testing in the paddy fields. The experimental result shown that the new develop penetrometer instrument can be used as an alternative instrument to measure soil pentration that eqquiped with soil moisture content data.AbstrakPenetrometer statis didesain untuk mengukur gaya yang dibutuhkan untuk menekan probe kerucut kedalaman tanah dengan kecepatan konstan. Output datanya adalah gaya persatuan luas tanpa faktor sifat tanah lain seperti kadar air. Kadar air tanah merupakan faktor penting yang memengaruhi tahanan penetrasi tanah. Metode pengukuran kadar air yang umum menggunakan metode gravimetri yang membutuhkan waktu cukup lama untuk mendapatkan data kadar air tanah. Maka dari itu dibutuhkan penetrometer yang dapat sekaligus mengukur kadar air dengan baik. Tujuan dari penelitian ini adalah merancang, membangun dan menguji penetrometer digital dilengkapi pembacaan kadar air dengan perekam data berbasis android. Loadcell dan HX711 digunakan sebagai sensor gaya, HC-SR04 dan DHT11 digunakan sebagai sensor kedalaman dan kit sensor kadar air tanah termodifikasi digunakan sebagai sensor kadar air. Hasil kalibrasi dan validasi sensor didapatkan nilai R2=0.9994 dan R2=0.9995 untuk sensor gaya, R2=0.9999 dan R2=0.9999 untuk sensor kedalaman, R2=0.9098 dan R2=0.9255 untuk sensor kadar air tanah. Hasil pengujian kinerja di lahan kering secara terpadu di dapatkan nilai nilai R2=0.9583 untuk cone index, R2=0.9994 untuk sensor kedalaman dan R2=0.6673 untuk sensor kadar air. Hasil pengujian di lahan sawah didapatkan nilai R2=0.9583 untuk sensor gaya, R2=0.9941 untuk sensor kedalaman dan R2=0.7696 untuk sensor kadar air. Hasil analisis regresi pada proses kalibrasi ulang didapat persamaan penduga kadar air dengan nilai R2=0.7201 untuk pengujian di lahan kering dan R2=0.9058 untuk pengujian di lahan sawah. Berdasarkan data yang didapatkan maka penetrometer yang dirancang dapat digunakan sebagai alternatif instrumen ukur tahanan penetrasi yang dilengkapi dengan data kadar air.